Differences in Learning Outcomes and Science Process Skills of Students Learned with the Model Project Based Learning and Discovery Learning on Acid-Base Material - Sembiring, Niki Arih Ersada Br; Jahro, Iis Siti (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The purpose of this study is to determine the differences in learning outcomes and science process skills of students learned with Project Based Learning and Discovery Learning models on acid-base material, as well as the correlation between students' science process skills and student learning outcomes. This research is a quantitative research. The samples in this study were taken by random sampling of 2 classes, namely XI MIPA 1 as experimental class I and XI MIPA 3 as experimental class II, where each class was taken by 29 students based on the similarity of pretest results. The instruments used are test instruments in the form of multiple-choice questions and essays and non-test instruments in the form of observation sheets. Hypothesis testing was carried out using the SPSS Statistic version 24 for Windows computer program using the Independent Sample T-Test and Bivariate Pearson Correlation. For hypothesis I obtained the value of sig. (2-tailed) 0.008   (0.05) so that Ha is accepted, which means that there are differences in student learning outcomes learned with Project Based Learning and Discovery Learning models on acid-base material. For hypothesis II obtained sig value. (2-tailed) 0.010   (0.05) so that Ha is accepted, which means that there are differences in students' science process skills learned with the Project Based Learning and Discovery Learning models on acid-base material. For hypotheses III and IV obtained sig values. (2-tailed) of 0.002 and 0.001  (0.05) so that Ha is accepted, which means that there is a correlation between students' science process skills and student learning outcomes learned with Project Based Learning and Discovery Learning models on acid-base material.